2013
DOI: 10.1186/1477-7819-11-123
|View full text |Cite
|
Sign up to set email alerts
|

Tumor suppressor gene RBM5 delivered by attenuated Salmonella inhibits lung adenocarcinoma through diverse apoptotic signaling pathways

Abstract: BackgroundRBM5 (RNA-binding motif protein 5, also named H37/LUCA-15) gene from chromosome 3p21.3 has been demonstrated to be a tumor suppressor. Current researches in vitro confirm that RBM5 can suppress the growth of lung adenocarcinoma cells by inducing apoptosis. There is still no effective model in vivo, however, that thoroughly investigates the effect and molecular mechanism of RBM5 on lung adenocarcinoma.MethodWe established the transplanted tumor model on BALB/c nude mice using the A549 cell line. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 36 publications
4
17
0
Order By: Relevance
“…Rac1 and β-catenin were upregulated when RBM5 was knocked down [ 26 ]. Our previous study confirmed previous findings and further demonstrated that exogenous expression of RBM5 inhibited the A549 cell growth in vivo and in vitro , and re-sensitized A549/DDP cells to cisplatin by enhancement of mitochondria apoptosis [ 18 , 19 , 21 ]. Our recent study demonstrated for the first time an inverse correlation between the expression levels of RBM5 , and transforming growth factor alpha (TGF-α) signaling factors, EGFR , and KRAS in NSCLC tissues [ 22 ], which suggested that the presence of a complex regulatory network between those genes was involved in tumor suppression and oncogenic expression.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Rac1 and β-catenin were upregulated when RBM5 was knocked down [ 26 ]. Our previous study confirmed previous findings and further demonstrated that exogenous expression of RBM5 inhibited the A549 cell growth in vivo and in vitro , and re-sensitized A549/DDP cells to cisplatin by enhancement of mitochondria apoptosis [ 18 , 19 , 21 ]. Our recent study demonstrated for the first time an inverse correlation between the expression levels of RBM5 , and transforming growth factor alpha (TGF-α) signaling factors, EGFR , and KRAS in NSCLC tissues [ 22 ], which suggested that the presence of a complex regulatory network between those genes was involved in tumor suppression and oncogenic expression.…”
Section: Discussionsupporting
confidence: 91%
“…The use of animals in this study was in accordance with animal care guidelines, and the protocol was approved by Jilin University Animal Care Committee. A549 xenografts were established and the RBM5 gene was delivered into xenografts by attenuated Salmonella according to a previous study [ 19 ]. Briefly, BALB/c athymic nude female mice (nu/nu); between four and five-weeks-old) were purchased from the Institute of Zoology, Chinese Academy of Sciences (Beijing, China).…”
Section: Methodsmentioning
confidence: 99%
“…is able to regulate apoptosis and cell cycle progression by increasing signal transducer and activator of transcription 5B and bone morphogenetic protein 5 expression levels, and reducing nuclear receptor coactivator 3, Pim-1 proto-oncogene serine/threonine kinase, baculoviral IAP repeat containing 3, BCL-2, EGFR and cyclin dependent kinase 2 expression levels (44)(45)(46)(47). In addition, RBM5 was demonstrated to inhibit cyclin A expression and RB phosphorylation, and thereby regulate cell cycle progression and induce G1 arrest (30).…”
Section: Function Of Rbm5 In Human Cellsmentioning
confidence: 99%
“…The ectopic expression of RBM5 suppresses the growth of human lung cancer [ 11 ], breast cancer [ 13 ], fibrosarcoma [ 14 ], and hematopoietic cells [ 15 17 ]. Our previous study demonstrated that exogenous expression of RBM5 by the pcDNA3.1-RBM5 inhibited the cell growth of human prostate cancer and lung cancer in vivo and in vitro and resensitized the response of A549/DDP cells (cisplatin resistant counterparts of A549 cells) to cisplatin [ 8 , 18 20 ]. Although the mechanisms of RBM5-mediated tumor suppression remain not quite clear, recent studies suggest that RBM5 is involved in the regulation of the mitochondrial apoptotic pathway and Bcl-2 family expression [ 8 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study demonstrated that exogenous expression of RBM5 by the pcDNA3.1-RBM5 inhibited the cell growth of human prostate cancer and lung cancer in vivo and in vitro and resensitized the response of A549/DDP cells (cisplatin resistant counterparts of A549 cells) to cisplatin [ 8 , 18 20 ]. Although the mechanisms of RBM5-mediated tumor suppression remain not quite clear, recent studies suggest that RBM5 is involved in the regulation of the mitochondrial apoptotic pathway and Bcl-2 family expression [ 8 , 18 , 19 ]. It has been confirmed that Bcl-2 family also function as autophagy regulators via their interaction with the core autophagy factor Beclin family which plays an important role in the initiation of autophagosome formation [ 21 24 ].…”
Section: Introductionmentioning
confidence: 99%